Demented Particulars - Ackerley, Chris,Gontarski, S. E. (Edinburgh University Press, 2010)
This is a detailed, page by page annotation of Samuel Beckett's first published novel, Murphy. In the introduction, Ackerley outlines the history of the novel and the critical debate surrounding it. He gives an account of the vast range of reading that directly influenced Murphy, and a presents a sophisticated discussion of the 'Cartesian catastrophe' at the heart of it. He also includes an extensive bibliography and a thematic index. Visit Chris Ackerley's Homepage
10.1515/9780748643257